what is the first step in solving for x in the equation 5.6(+1.42)=7.8 only the left hand side was divided 5.6 multiply both sides by 6 divided both sides by 6

3 answers

The first step in solving for x in the equation 5.6x + 1.42 = 7.8 is to subtract 1.42 from both sides of the equation. This will give you:

5.6x = 7.8 - 1.42

Now, simplify the right-hand side of the equation:

5.6x = 6.38

The equation has been simplified to a single term on the left-hand side.
are you sure\?
Apologies for the confusion. I made a mistake in my response.

To solve for x in the equation 5.6x + 1.42 = 7.8, the first step is to subtract 1.42 from both sides of the equation. This will give you:

5.6x = 7.8 - 1.42

Simplifying the right-hand side:

5.6x = 6.38

Thank you for pointing out the error, and I apologize for any confusion caused.